Analysis of the Implementation of the Merdeka Belajar Curriculum at SMAN 2 Taliwang - Fajrin, Maghfiroh; ramdani, novi; Akbar, Filza; Muhaji, Muhaji; Hikma, Sarah Nikmatul (JUPE : Jurnal Pendidikan Mandala, 2023)
This study aims to identify the application of the independent curriculum at SMAN 2 Taliwang. The research method used in this study is qualitative descriptive. Data collection techniques use observation and interview techniques. The data analysis technique consists of three stages, namely data reduction, data presentation, and conclusions. The results showed that the implementation of the Merdeka Belajar curriculum at SMAN 2 Taliwang went well. Students are more active because they can explore their learning interests, which adequate educational facilities support.